Electrical Removal Behavior of Carbon Nanotube and Carbon Nanofiber Film in CuCl2 Solution: Kinetics and Thermodynamics Study - Yankun Zhan; Chunyang Nie; Likun Pan; Haibo Li; Zhuo Sun (International Journal of Electrochemistry)
The kinetics, thermodynamics, and isotherms during electrical removal of Cu2+ by carbon nanotube and carbon nanofiber (CNT-CNF) electrodes in CuCl2 solution were studied under different solution temperatures, initial Cu2+ concentrations, and applied voltages. The result shows that Langmuir isotherm can describe experimental data well, indicating monolayer adsorption, and higher Cu2+ removal and rate constant are achieved at higher voltage, lower initial Cu2+ concentration, and higher solution temperature. Meanwhile, the thermodynamics analyses indicate that the electrical removal of Cu2+ onto CNT-CNF electrodes is mainly driven by a physisorption process.